2014
DOI: 10.1039/c4dt00087k
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably enhanced photocatalytic activity of ordered mesoporous carbon/g-C3N4 composite photocatalysts under visible light

Abstract: Ordered mesoporous carbon/g-C3N4 (OMC/g-C3N4) composites with efficient photocatalytic activity under visible light irradiation were prepared by a facile heating method. The as-prepared OMC/g-C3N4 composites were thoroughly characterized by X-ray diffraction, Fourier transform infrared spectroscopy, elemental analyses, transmission electron microscopy with energy dispersion X-ray spectroscopy, N2 adsorption-desorption analysis, UV-vis diffuse reflectance spectroscopy and photoluminescence spectroscopy. The pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 48 publications
2
73
0
Order By: Relevance
“…However,n oc lear diffraction peak for carbon was observed in any of the composites;t his might be due to the lower content or high dispersity of carbon in the composites. [12] X-ray photoelectron spectroscopy (XPS) measurements were performed to further determine the chemical composition and valence state of various species. Figure2displays the high-resolution spectra of Zn 2p,A g3d, C1s, and O1sf or the Ag/ mC/CÀZnO-2 composites.…”
Section: Resultsmentioning
confidence: 99%
“…However,n oc lear diffraction peak for carbon was observed in any of the composites;t his might be due to the lower content or high dispersity of carbon in the composites. [12] X-ray photoelectron spectroscopy (XPS) measurements were performed to further determine the chemical composition and valence state of various species. Figure2displays the high-resolution spectra of Zn 2p,A g3d, C1s, and O1sf or the Ag/ mC/CÀZnO-2 composites.…”
Section: Resultsmentioning
confidence: 99%
“…The asymmetric unit of 1 consists of one independent Zn II atom, one 3-npa ligand, and one btbp ligand. As depicted in Figure S2a (Supporting Information), the crystallographically independent central Zn II atom is hexacoordinated by four nitrogen atoms (N1, N2, N4, and N5) from two btbp ligands and two oxygen atoms (O3 and O4) belonging to one 3-npa ligand giving rise to a distorted octahedral coordination arrangement {CoN 4 In complex 1, the two carboxy groups of each 3-npa ligand adopt different coordination modes: one coordinates to a Zn II atom with a chelating mode, whereas the other one is protonated. Each trans-btbp ligand, in which the dihedral angles between the mean planes of two benzimidazole rings is 82.89(13)°, acts as μ 2 -bridging linker between adjacent Zn II atoms to form a fascinating meso-helical chain with left-and right-handed helical loops in one single strand along the a axis (Figure 1a).…”
Section: Crystal Structure Of [Zn(btbp)(3-npa)] N (1)mentioning
confidence: 99%
“…As depicted in Figure S3 (Supporting Information), the overall coordination arrangement of the central Co II atom can be described as a distorted octahedron coordination arrangement {CoN 4 Complex 3 crystallizes in the triclinic space group P1. In the asymmetrical unit of 3, there exists one crystallographically independent Co II atom, one 5-nipa ligand, one btbb ligand, one coordinated water molecule and one lattice water molecule.…”
Section: Crystal Structure Of [Co(btbh)(3-npa)] N (2) and {[Co(btbb)(mentioning
confidence: 99%
See 1 more Smart Citation
“…To identify and quantify the dominating reactive species in the photodegradation process over g-C 3 N 4 /Bi 12 were respectively added into photocatalytic system, which served as scavenger to quench cO 2 À , h + and cOH. [49][50][51][52] As shown in Fig. 8, aer AA and EDTA-2Na were added into the photocatalytic reaction system, respectively, it was clearly observed that the photodegraded activity of the g-C 3 N 4 /Bi 12 O 17 Cl 2 composite was sharply declined, meaning that cO 2 À and h + radical were the key active species in this reaction.…”
Section: -40mentioning
confidence: 99%